2021
DOI: 10.1007/s10750-021-04712-9
|View full text |Cite
|
Sign up to set email alerts
|

Fish morphology and passage through velocity barriers. Experience with northern straight-mouth nase (Pseudochondrostoma duriense Coelho, 1985) in an open channel flume

Abstract: Knowing the relationship between size, morphological traits and swimming performance of fish is essential to understand the swimming capacity to successfully surpass these obstacles and the selective pressure that barriers in rivers and streams could exert on fish. Northern straight-mouth nase, an endemic potamodromous cyprinid fish species from the Northwest of the Iberian Peninsula, was selected to carry out volitionally swimming performance experiments in an open channel against three different flow velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Swimming performance is affected by behavioural processes, and fish are expected to be much more motivated to pass velocity barriers during the reproductive season, when, in the case of cyprinids, the temperature increases (García-Vega et al, 2022), or falls in the case of salmonids (Goerig et al, 2017). Moreover, differences in the swimming ability of fish are expected in other reaches and habitats, directly related to their morphology or their genetic origin (Alexandre et al, 2014;Sánchez et al, 2022), which must be considered. Therefore, despite the fact that thermal response of swim speed could be somehow predictable, the ecological, physiological and phylogenetic factors that underlie the relationship remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swimming performance is affected by behavioural processes, and fish are expected to be much more motivated to pass velocity barriers during the reproductive season, when, in the case of cyprinids, the temperature increases (García-Vega et al, 2022), or falls in the case of salmonids (Goerig et al, 2017). Moreover, differences in the swimming ability of fish are expected in other reaches and habitats, directly related to their morphology or their genetic origin (Alexandre et al, 2014;Sánchez et al, 2022), which must be considered. Therefore, despite the fact that thermal response of swim speed could be somehow predictable, the ecological, physiological and phylogenetic factors that underlie the relationship remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Wardle (1978) found that after an 8 h rest, the 50%-80% of the muscle glycogen is restored. In particular, swimming experiments in fishways with confined and reused fish showed no variations in the swimming performance after 12 h resting (Bravo-C ordoba et al, 2018;Sanz-Ronda et al, 2019). Therefore, the 12 h recovery period among consecutive tests should be sufficient for the fish to restore the muscle glycogen and metabolize most part of lactate.…”
Section: Trialsmentioning
confidence: 99%
“…Simulations showed that a high initial velocity or a low downstream water level (e.g., due to scouring or other river geomorphological features) will provoke greater magnitudes of velocities in the downstream face and immediately after it, surpassing fish swimming capability even for the observed passable discharge ranges. Moreover, differences in the swimming ability of fish are expected in other reaches and habitats, directly related to their sizes [16], their morphology [17], or their genetic origin [52], which must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This enlarges the area with high velocities and low depths (hydraulic barrier) below the weir [11], further reducing, the fish passage probability. Furthermore, weirs can act as selective barriers since the swimming and leaping ability of fish is directly related to fish size and morphology, which may have further implications on the behavioral and dispersal processes of fish populations [16,17]. Habitat fragmentation caused by river barriers is among the main causes of the global decline in freshwater biodiversity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some notable results of the VIII Iberian Congress of Ichthyology are presented in this Themed Section with two guest editors, Javier Sánchez-Hernández and Rufino Vieira-Lanero, who managed the peer review process. This Themed Section covers various aspects of marine and freshwater fish biology that were presented at this congress such as fish migration (García-Vega et al, 2021), conservation status (Miqueleiz et al, 2021), swimming performance (Sánchez-González et al, 2021) and population structure (Schroeder et al, 2021). It should be noted that this Themed section presents papers of the meeting, and that although most papers covered the Iberian Peninsula (García-Vega et al, 2021;Miqueleiz et al, 2021;Sánchez-González et al, 2021), there is one focused on Brazilian fishery grounds (Schroeder et al, 2021).…”
Section: Abstract Fish Biology • Iberian Fish • Ichthyofaunamentioning
confidence: 99%